2009
DOI: 10.1111/j.1467-9566.2008.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing nature of prescribing: pharmacists as prescribers and challenges to medical dominance

Abstract: This paper investigates the potential threat to medical dominance posed by the addition of pharmacists as prescribers in the UK. It explores the role of prescribing as an indicator of professional power, the legitimacy and status of new pharmacist prescribers and the forces influencing professional jurisdictional claims over the task of prescribing. It draws upon 23 interviews with pharmacist supplementary prescribers. Data suggest that the legitimacy of pharmacists as prescribers, as experienced in the workpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 24 publications
2
96
0
1
Order By: Relevance
“…This mirrors what has been reported in earlier studies of pharmacist prescribing; Lloyd et al [13] reported that there were major concerns voiced over pharmacist involvement in diagnosis as doctors considered this their defining role and appreciated that pharmacists themselves would be uncomfortable with diagnosis. Similarly, were two aspects of the prescribing process where pharmacists felt the least competent: conducting clinical examinations and making initial diagnostic decisions [20]. Pharmacists in this study [20] conveyed that they were not used to carrying out physical examinations of patients and many had selected pharmacy as a profession because they did not want 'to get their hands dirty' [20].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This mirrors what has been reported in earlier studies of pharmacist prescribing; Lloyd et al [13] reported that there were major concerns voiced over pharmacist involvement in diagnosis as doctors considered this their defining role and appreciated that pharmacists themselves would be uncomfortable with diagnosis. Similarly, were two aspects of the prescribing process where pharmacists felt the least competent: conducting clinical examinations and making initial diagnostic decisions [20]. Pharmacists in this study [20] conveyed that they were not used to carrying out physical examinations of patients and many had selected pharmacy as a profession because they did not want 'to get their hands dirty' [20].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, were two aspects of the prescribing process where pharmacists felt the least competent: conducting clinical examinations and making initial diagnostic decisions [20]. Pharmacists in this study [20] conveyed that they were not used to carrying out physical examinations of patients and many had selected pharmacy as a profession because they did not want 'to get their hands dirty' [20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…NMPs assert that they adhere strictly to evidence-based practice (28) , yet this may not always be the case (32,33) . NMPs have disparate professional backgrounds but unlike doctors, none comes from a tradition of sometimes paternalistic relationships with patients or from a position at the top of the healthcare hierarchy (34,35) . It may be that their prescribing decisions are informed by different or additional influences to those of doctors.…”
Section: Introductionmentioning
confidence: 99%